Faktor-Faktor Yang Mempengaruhi Kemauan Wajib Pajak Orang Pribadi Untuk Mengikuti Tax Amnesty (Studi Empiris Pada Perguruan Tinggi Di Jakarta Barat) - Viriany, Yanti, Henny Wirianata, Liana Susanto, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2018)
The purpose of this research was to obtained an empirical evidence about the influence of continuous Government’s campaign, easiness of tax amnesty, tax amnesty’s rate, and tax sanctions on taxpayer’s willingness to enroll tax amnesty. This study use primary data from quesioners. Continuous Government’s campaign measured by 5 questions, easiness of tax amnesty 7 questions, tax amnesty’s rate 7 questions, tax sanctions 2 questions, and taxpayer’s willingnes 4 questions. The respondents were Lecturers in Economic Faculty in Tarumanagara University. This study used statistical tests. The results showed that continuous Government’s campaign and easiness of tax amnesty have sifnificant and positive influence toward taxpayer’s willingness. Meanwhile, tax amnesty’s rate and tax sanctions has no significant influence toward taxpayer’s willingness to enroll tax amnesty.